New FOPID Control Design for Flight Dynamics With Special Phenomena - Sir Elkhatem, Aisha; Engin, Seref Naci; Malik, Zainab (WILEY, 2025)
The design of a flight control system (FCS) for aircraft altitude change dynamics presents significant challenges due to the inherent non-minimum phase (NMP) behavior. This behavior leads to undesirable initial undershoot responses, imposing significant limitations on internal stability and severely restricting the performance and robustness of directly applying conventional control methods. Despite the widespread use of proportional-integral-derivative (PID) controllers in industrial applications, their robustness, performance, and disturbance rejection deteriorate when applied to systems exhibiting NMP characteristics. This paper highlights the practical importance of upgrading PID-based controllers for flight dynamics with NMP behavior by addressing these challenges, with a particular focus on tracking and stability issues under direct feedback control. To overcome these limitations, we propose a modified control architecture incorporating a fractional-order PID (FOPID) controller, augmented with a fractional-order derivative filtering component (FD). This design aims to enhance transient response, noise immunity, and adaptability without adding significant complexity. The control problem is framed as a single-objective optimization task, where the Particle Swarm Optimization (PSO) algorithm is used to simultaneously tune the proposed controller gains, minimizing the error between the actual and desired altitude commands. The performance of the proposed controller was compared to traditional PID and FOPID controllers through both time and frequency domain analyses, under scenarios involving parametric uncertainty and 50% and 80% loss of effectiveness in the actuator (elevator) fault. The performance evaluation was based on transient response criteria, while robustness was assessed in terms of delay, phase, and gain margins. The simulation results show that under nominal flight conditions, the proposed controller significantly outperforms conventional FOPID controllers, reducing the percent overshoot from 52% to 2% for the Integral Absolute Error (IAE), from 44% to 2% for the Integral Time Squared Error (ITSE), and from 60% to 3% for the Integral Time Absolute Error (ITAE) performance metrics. The robustness analysis reveals that even under extreme conditions, such as system uncertainties, 50% and 80% actuator loss, the proposed controller maintains stability. Across these cases, it achieves a minimum phase margin of 158 degrees and a gain margin of 13.3 dB, in contrast to the 27.8 degrees and 16.4 dB observed with conventional controllers. These findings underscore the controller's efficacy in providing reliable and robust altitude control in real-world flight conditions, even under significant actuator degradation and system uncertainties.
Keywords: actuator faults; bandwidth constraints; FOPID controller; internal stability; non-minimum phase (NMP) dynamics; PSO; reverse response; right-half plane (RHP) zeros; FLY-BY-WIRE; PHASE; PERSPECTIVE; TRACKING; SYSTEMS; Automation & Control Systems; Operations Research & Management Science; Mathematics